Appreciation of Prosperity Gospel’s missional message and the cause to rethink its dismissive criticism - Adegbile, Wole; Adegbile, Jackie (Stellenbosch Theological Journal, 2025)
This study examines the missional message of the Prosperity Gospel against the mainstream definition of the gospel. It seeks to find out if there is something biblical about its proclamation to the people. In its missional message, the teaching proclaims the identity of Christ as the Saviour of mankind rescuing them from eternal destruction. The study holds this as a starting point for reformative criticism of the Prosperity Gospel, which can be made better if criticised with its potential in mind and personal freedom from traditional biases on the parts of the critics.